2006
DOI: 10.1002/ijc.21346
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for simian virus 40 DNA sequences in malignant non-Hodgkin lymphomas

Abstract: DNA sequences coding for simian virus 40 (SV40) large T antigen have been detected at different frequencies in human non-Hodgkin's lymphomas (NHL) by PCR techniques as well as immunohistochemistry. A highly sensitive quantitative real-time PCR specific for a sequence of SV40 large T antigen was established to test whether SV40 DNA is present in malignant lymphomas of German patients. Thirty-three lymph node samples obtained from 27 patients with NHL and 6 patients with Hodgkin's disease (HD) were tested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Using PCR and subsequent Southern blotting, we have successfully demonstrated the presence of SV40 DNA sequences in 56% of DLBCLs in Tunisian patients prevalence, which is at the higher end of those reported from other countries. [12][13][14][15][16][17][18][19][20][21] However, these findings are at variance with those presented by other investigators, [22][23][24] who did not detect SV40 DNA in any of the lymphomas samples analyzed. This discrepancy in SV40 detection in lymphoma between several parts of the world is not clear, but it could be at least in part due to differences in laboratory techniques used for virus detection, the criteria of requirements for confirmation of the presence of virus, 1,19,22,54,56 the characteristics of patients populations that were the source of specimens 1,54 and mainly the difference in histological types of lymphomas tested.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Using PCR and subsequent Southern blotting, we have successfully demonstrated the presence of SV40 DNA sequences in 56% of DLBCLs in Tunisian patients prevalence, which is at the higher end of those reported from other countries. [12][13][14][15][16][17][18][19][20][21] However, these findings are at variance with those presented by other investigators, [22][23][24] who did not detect SV40 DNA in any of the lymphomas samples analyzed. This discrepancy in SV40 detection in lymphoma between several parts of the world is not clear, but it could be at least in part due to differences in laboratory techniques used for virus detection, the criteria of requirements for confirmation of the presence of virus, 1,19,22,54,56 the characteristics of patients populations that were the source of specimens 1,54 and mainly the difference in histological types of lymphomas tested.…”
Section: Discussionmentioning
confidence: 66%
“…11 There also increasing evidence that SV40 is associated with non-Hodgkin's lymphomas, particularly with diffuse large B-cell lymphomas (DLBCL), 12-21 in spite of several negative studies. [22][23][24] However, although these observations indicate an association between this virus and specific human tumors, they do not demonstrate a causal role, and the molecular mechanism by which SV40 thought to be involved is still unclear.SV40 oncogenic potential is assumed to be associated with the primary viral gene product, large T-antigen (Tag), protein responsible for SV40 replication and SV40-mediated cell transformation. 1 In vitro, the infection of human cells by SV40 has showed that SV40 Tag can promote malignancy transformation by blocking the products of several tumor suppressor genes (TSGs), 1,25 inducing telomerase activity, 26 and stimulating other oncogenes and growth factors.…”
mentioning
confidence: 97%
“…Using data from serological experiments, a number of investigators have demonstrated a lack of significant SV40 seroprevalence in patients with NHL [71][72][73][74]. Though these noted studies [71][72][73][74] relied solely on serological evidence, PCR has been used to show that SV40 DNA sequences were either of low incidence in comparison to controls or unable to be detected in NHL samples from a variety of countries, including the United States [75][76][77][78][79].…”
Section: Non-hodgkin Lymphomamentioning
confidence: 96%
“…There is strong evidence that SV40 can be found in humans today, both in those with and without malignancies. SV40 markers have been detected in tumor tissue from lymphoma patients in some studies1523 but not in others 2431. These discrepancies may reflect variations among sources of specimens, sample processing, or assays.…”
Section: Introductionmentioning
confidence: 98%